Models With LKS Jurisprudential Inquiry-Based Multi Representation - Julfa Salfini Fivturia; I Ketut Mahardika; Bambang Supriadi (Pancaran Pendidikan, 2017)
This study describes the learning by using the model with LKS jurisprudential inquiry-beside multi-representation. This study aims to determine the Jurisprudential inquiry learning model with LKS multi-representation the kinematics of rectilinear motion of matter in the high school. This research uses a descriptive method of qualitative research. The from data describing critical reviews written by experts from a documentation, interviews, proceedings or reference book and then the data is analysed as a clarification process and data grouping. The results showed that the jurisprudential inquiry learning model with LKS Multipresentasi on the material kinematics of rectilinear motion in high school can make learning more effective because students gain experience learned directly so that students understand the concept easily, it can improve learning outcomes and skills the ability of scientific process skill of the students.